Comparison of Lumbar Sacral Plexus Block with Spinal Anesthesia In High-Risk Patients Scheduled For Hip Surgeries (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: High risk elderly patients with hip fractures were the greatest challenge to anesthesiologist as they are more prone to perioperative morbidity and mortality. Combined lumbar sacral plexus block have been an effective method of anaesthesia, also considerable in postoperative analgesia in high-risk patients of hip surgeries as it provides fewer complications, better homeostasis, hemodynamic control. OBJECTIVES: The aim of this study was to compare the efficacy of lumbar sacral plexus block with subarachnoid block in terms of onset and duration of sensory and motor blockade, hemodynamic changes and postoperative analgesia. MATERIALS AND METHODS: This prospective randomized study was carried out in 50 patients aged 35-80 years and weighed 40 to 85 kg belonging to ASA physical status III/IV posted for hip surgeries. patients were divided into two groups, SAB (subarachnoid block) group and LSPB (lumbar sacral plexus block) group of 25 each by convenient sampling. Onset of sensory and motor blockade, hemodynamic changes, time for first rescue analgesic were noted and compared. Statistical analysis was done using SPSS Software. RESULTS: The perioperative heart rate and arterial blood pressure were more stable in LSPB group. Postop analgesia duration was significantly prolonged in LSPB group (11.4±1.7 hours) as compared to SAB group (4.3±0.43 hours). Hypotension and bradycardia noted in SAB group. CONCLUSION: Lumbo-sacral plexus block offered more stable intraoperative hemodynamic parameters and prolonged postop analgesia as compared to Subarachnoid block in high-risk patients undergoing hip surgeries.
Keywords: Lumbosacral plexus block; Spinal anaesthesia; Hip surgeries; Analgesia